High-conductivity sodium ion battery positive electrode material / organic conductive polymer composite material and preparation method thereof
By modifying the organic conductive polymer on the surface of Na2+xFe2-x(SO4)3, a three-dimensional conductive network is formed, which solves the problems of high temperature instability and low electronic conductivity of sulfate materials, and achieves a sodium ion battery positive electrode material with high conductivity and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411603474.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing sodium ion battery positive electrode material sulfate materials have problems of high temperature instability and low electronic conductivity, which makes it difficult for them to modify in situ carbon through high temperature pyrolysis, thereby enhancing electronic conductivity.
By modifying the organic conductive polymer on the surface of Na2+xFe2-x(SO4)3, a three-dimensional conductive network is formed to enhance the electronic conductivity of the material. The method includes the preparation of chain products, the preparation of precursor slurry, the preparation of precursor powder and the high-temperature sintering steps.
The sodium ion battery positive electrode material with high conductivity, low specific surface area, high compaction density and excellent electrochemical performance has been achieved, improving the electronic conductivity and rate performance of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a high-conductivity sodium ion battery positive electrode material / organic conductive polymer composite material and a preparation method thereof. Background Art
[0002] The performance of cathode materials has a significant impact on the energy density and electrochemical performance of sodium-ion battery systems. Sodium-ion battery materials that are truly suitable for mass production need to meet the characteristics of low cost, high performance, and easy processing. However, the layered oxides, Prussian blue systems, and polyanion materials currently available on the market have different performances, and there are few materials with excellent comprehensive performance.
[0003] As a branch of the positive electrode materials of polyanion sodium ion batteries, sulfate materials have abundant resource reserves, simple preparation process, high voltage platform, and high system energy density. The market currently positions them in the low-end power field. However, sulfate materials are high-temperature unstable phases. When the temperature is higher than 450°C, the sulfate in the material is very easy to decompose to form sulfur dioxide. Therefore, the sintering temperature of the material is generally low. In addition, the material is a three-dimensional framework structure in which FeO6 octahedrons and SO4 tetrahedrons are interconnected in the form of common points / lines / surfaces. Because SO4 is not conductive, the electronic conductivity of the material is generally low. However, the high-temperature instability of the material makes it difficult to perform in-situ carbon modification through high-temperature pyrolysis to improve electronic conductivity. At present, the commonly used method on the market is to physically mix inorganic carbon (carbon nanotubes, graphene, high specific surface carbon black) with sulfate materials, which will cause the material specific surface to be too large. At the same time, the cost of the above-mentioned inorganic carbon is too high, causing sulfate materials to lose their own unique low-cost advantage. Summary of the invention
[0004] The purpose of the present invention is to provide a high-conductivity sodium ion battery positive electrode material / organic conductive polymer composite material and a preparation method thereof, which has the characteristics of high electronic conductivity, low specific surface area, high compaction density and excellent electrochemical performance.
[0005] The present invention can be implemented by the following technical solutions: The invention discloses a method for preparing a high-conductivity sodium ion battery positive electrode material / organic conductive polymer composite material, comprising the following steps: S1. Preparation of chain products: dissolving organic conductive polymer monomers in water, adjusting the pH of the solution to acidic, adding an oxidant, and inducing a polymerization reaction of the organic conductive polymer monomers to form chain products; S2. Preparation of precursor slurry: adding a sodium source, an iron source and a sulfur source to the solution for forming the chain product, and dissolving them fully to form a uniform precursor slurry; S3, preparation of precursor powder: drying the above-mentioned precursor slurry to achieve solid-liquid separation to obtain dry precursor powder; S4, high temperature sintering: calcine the above precursor powder in a protective atmosphere, and obtain Na after natural cooling. 2+x Fe 2-x (SO4)3 / organic conductive polymer composite positive electrode material; In Na 2+x Fe 2-x In the (SO4)3 / organic conductive polymer composite positive electrode material, the value range of x is 0≤x≤1.
[0006] In the present invention, in order to improve the electronic conductivity of sulfate materials. The present invention prepares Na 2+x Fe 2-x (SO4)3 / organic conductive polymer positive electrode material, which is characterized by 2+x Fe 2-x (SO4)3 is surface-modified with an organic conductive polymer, which is a chain structure formed by the polymerization of organic compound monomers containing double bonds. This structure has the ability to conduct electrons. 2+x Fe 2-x The (SO4)3 particles form a three-dimensional conductive network, which will greatly improve the electronic conductivity at the interface of the material. The process is simple to operate, and the prepared material has high uniformity, small specific surface area, and excellent electrochemical performance.
[0007] Furthermore, the organic conductive polymer is one or more of polyaniline, polypyrrole, polythiophene, polyacetylene, polyphenylene, polyphenylene acetylene, and polydiacetylene; the organic conductive polymer monomer is one or more of aniline, pyrrole, thiophene, acetylene, phenylene, and diacetylene.
[0008] Furthermore, in step S1, the pH range is 1-4. When the pH is lower than 1, the corrosion intensity to the equipment is large, which is not conducive to large-scale production. When the pH is higher than 4, the proton hydrogen content in the solution is not enough to support the cross-linking reaction of the organic conductive polymer monomer, affecting the polymerization effect.
[0009] Furthermore, in step S1, the oxidant is one or more of hydrogen peroxide, hydrazine hydrate, peracetic acid, and sodium percarbonate, and the added molar amount of the oxidant is 1-3 times the molar amount of the organic conductive polymer monomer. When the molar amount of the oxidant is less than 1 time, the organic conductive polymer monomer does not react fully, and there are problems such as partial waste of raw materials. When the molar amount of the oxidant is higher than 3 times, excess oxidant will increase production costs, and a large amount of residual oxidant will also affect the crystallization of subsequent materials.
[0010] Further, in step S4, the sintering temperature is 300-450°C, the time is ≥0.1H, and when the temperature is lower than 300°C, Na 2+x Fe 2-x The crystallinity of (SO4)3 crystals is low, and the uniformity of melt diffusion between structural elements decreases. 2+x Fe 2-x The (SO4)3 / organic conductive polymer interface has insufficient compactness, which affects the electrochemical performance of the material. When the temperature is higher than 450°C, Na 2+x Fe 2-x (SO4)3 crystals will melt and decompose at high temperatures, forming impurities and other problems, resulting in loss of material capacity.
[0011] Furthermore, in step S3, the drying method is one of spray drying, flash drying, and heating evaporation, or a combination of two or more thereof.
[0012] Furthermore, in step S1, the acid for adjusting pH is one or more of formic acid, acetic acid, sulfuric acid, nitric acid, citric acid, ascorbic acid, salicylic acid, and malic acid.
[0013] Further, in step S2, the sodium source is one or more of sodium formate, sodium acetate, sodium nitrate, sodium bicarbonate, sodium carbonate, sodium hydroxide, sodium sulfate, sodium citrate, and sodium ascorbate; the iron source is one or more of iron powder, ferrous sulfate, ferric hydroxide, ferrous oxide, ferroferric oxide, ferric oxide, ferric hydroxide, and ferric hydroxide; the sulfur source is one or more of sulfuric acid, ammonium sulfate, sodium sulfate, ferrous sulfate, and ammonium ferrous sulfate.
[0014] Furthermore, in step S4, the protective atmosphere is one or more of nitrogen, argon, carbon monoxide, carbon dioxide, hydrogen, and helium.
[0015] Another aspect of the present invention is to protect a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material, which is prepared by the above preparation method.
[0016] The present invention discloses a high-conductivity sodium ion battery positive electrode material / organic conductive polymer composite material and a preparation method thereof, which has the following beneficial effects: First, the electronic conductivity is high. Organic conductive polymers such as polyaniline, polypyrrole, polythiophene and other components have a long-range π electron main chain structure. Under the action of an external electric field, the internal carriers (solitons, polarons and bipolarons) move along the conjugated π bonds, thereby achieving directional transfer of electrons and showing conductivity. This type of organic conductive polymer is attached to the material interface, which can achieve rapid conduction of electrons between material particles and between materials and polymers, thereby reducing the internal resistance polarization of the material.
[0017] Second, the specific surface area is low. The chain structure formed by the organic conductive polymer has a small specific surface area. At the same time, the dense and smooth crystal structure of the sulfate itself also makes it have a low specific surface area. 2+x Fe 2-x The specific surface area of the composite material of (SO4)3 / organic conductive polymer is not large. Compared with the sulfate materials modified with inorganic high specific surface carbon currently on the market, the smaller the specific surface area, the easier it is to make the subsequent battery cell electrode.
[0018] Third, the compaction density is high, Na 2+x Fe 2-x (SO4)3 / organic conductive polymer materials have no obstacles such as inorganic carbon during the sintering process, so Na 2+x Fe 2-x After the (SO4)3 material crystal nucleates, it can continue to grow epitaxially to form larger single crystal particles, while the chain structure of the organic conductive polymer has little effect on the epitaxy of the material. 2+x Fe 2-x (SO4)3 / organic conductive polymer has relatively dense primary particles and larger compaction density.
[0019] Fourth, the electrochemical performance is excellent. The present invention adopts the liquid phase method to prepare Na 2+x Fe 2-x (SO4)3 material has high element uniformity, and the crystal structure formed during the sintering process is relatively complete, with high phase purity and high capacity. At the same time, the uniform distribution of organic conductive polymers on the surface of the material increases the speed of electron transmission and reduces the polarization inside the material, effectively improving the rate performance of the material. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0021] The invention discloses a method for preparing a high-conductivity sodium ion battery positive electrode material / organic conductive polymer composite material, comprising the following steps: S1. Preparation of chain products: dissolving organic conductive polymer monomers in water, adjusting the pH of the solution to acidic, adding an oxidant, and inducing a polymerization reaction of the organic conductive polymer monomers to form chain products; S2. Preparation of precursor slurry: adding a sodium source, an iron source and a sulfur source to the solution for forming the chain product, and dissolving them fully to form a uniform precursor slurry; S3, preparation of precursor powder: drying the above-mentioned precursor slurry to achieve solid-liquid separation to obtain dry precursor powder; S4, high temperature sintering: calcine the above precursor powder in a protective atmosphere, and obtain Na after natural cooling. 2+x Fe 2-x (SO4)3 / organic conductive polymer composite positive electrode material; In Na 2+x Fe 2-x In the (SO4)3 / organic conductive polymer composite positive electrode material, the value range of x is 0≤x≤1.
[0022] Furthermore, the organic conductive polymer is one or more of polyaniline, polypyrrole, polythiophene, polyacetylene, polyphenylene, polyphenylene acetylene, and polydiacetylene; the organic conductive polymer monomer is one or more of aniline, pyrrole, thiophene, acetylene, phenylene, and diacetylene.
[0023] Further, in step S1, the pH range is 1-4.
[0024] Furthermore, in step S1, the oxidant is one or more of hydrogen peroxide, hydrazine hydrate, peracetic acid, and sodium percarbonate, and the added molar amount of the oxidant is 1-3 times the molar amount of the organic conductive polymer monomer.
[0025] Further, in step S4, the sintering temperature is 300-450°C, and the time is ≥0.1H.
[0026] Furthermore, in step S3, the drying method is one of spray drying, flash drying, and heating evaporation, or a combination of two or more thereof.
[0027] Furthermore, in step S1, the acid for adjusting pH is one or more of formic acid, acetic acid, sulfuric acid, nitric acid, citric acid, ascorbic acid, salicylic acid, and malic acid.
[0028] Further, in step S2, the sodium source is one or more of sodium formate, sodium acetate, sodium nitrate, sodium bicarbonate, sodium carbonate, sodium hydroxide, sodium sulfate, sodium citrate, and sodium ascorbate; the iron source is one or more of iron powder, ferrous sulfate, ferric hydroxide, ferrous oxide, ferroferric oxide, ferric oxide, ferric hydroxide, and ferric hydroxide; the sulfur source is one or more of sulfuric acid, ammonium sulfate, sodium sulfate, ferrous sulfate, and ammonium ferrous sulfate.
[0029] Furthermore, in step S4, the protective atmosphere is one or more of nitrogen, argon, carbon monoxide, carbon dioxide, hydrogen, and helium.
[0030] Another aspect of the present invention is to protect a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material, which is prepared by the above preparation method.
[0031] Example 1 This embodiment relates to a method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material, comprising the following steps: S1. Preparation of chain products: dissolving organic conductive polymer monomers in water, adjusting the solution pH to 4, adding oxidants, inducing polymerization of organic conductive polymer monomers to form chain products. Specifically, the organic conductive polymer monomer is aniline. The oxidant is hydrogen peroxide, and the added molar amount of the oxidant is twice the molar amount of the organic conductive polymer monomer; the acid for adjusting the pH is formic acid.
[0032] S2. Preparation of precursor slurry: Add sodium source, iron source and sulfur source to the solution for forming chain products, and dissolve them fully to form a uniform precursor slurry. The sodium source is sodium formate; the iron source is ferric hydroxide and ferrous oxide; the sulfur source is sulfuric acid and ammonium sulfate.
[0033] S3, preparation of precursor powder: drying the above precursor slurry to achieve solid-liquid separation, and obtaining dry precursor powder. Specifically, the drying method is spray drying.
[0034] S4, high temperature sintering: calcine the above precursor powder in a protective atmosphere, and obtain Na after natural cooling. 2+x Fe 2-x (SO4)3 / organic conductive polymer composite positive electrode material. Specifically, the sintering temperature is 300°C, the time is 1H, and the protective atmosphere is nitrogen.
[0035] In Na 2+x Fe 2-x In the (SO4)3 / organic conductive polymer composite positive electrode material, the value range of x is 0≤x≤1.
[0036] Example 2 This embodiment relates to a method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material, comprising the following steps: S1. Preparation of chain products: dissolving organic conductive polymer monomers in water, adjusting the solution pH to 2, adding oxidants, inducing polymerization of organic conductive polymer monomers to form chain products. Specifically, the organic conductive polymer monomers are aniline and pyrrole. The oxidant is peracetic acid, and the added molar amount of the oxidant is 1 times the molar amount of the organic conductive polymer monomer; the acid for adjusting the pH is acetic acid and sulfuric acid.
[0037] S2. Preparation of precursor slurry: Add sodium source, iron source and sulfur source to the solution for forming chain products, and dissolve them fully to form a uniform precursor slurry. The sodium source is sodium nitrate, sodium bicarbonate, sodium ascorbate; the iron source is ferric oxide, ferric hydroxide; the sulfur source is ferrous sulfate, ammonium ferrous sulfate.
[0038] S3, preparation of precursor powder: drying the above precursor slurry to achieve solid-liquid separation, and obtaining dry precursor powder. Specifically, the drying method is flash drying.
[0039] S4, high temperature sintering: calcine the above precursor powder in a protective atmosphere, and obtain Na after natural cooling. 2+x Fe 2-x (SO4)3 / organic conductive polymer composite positive electrode material. Specifically, the sintering temperature is 450°C, the time is 0.5H, and the protective atmosphere is carbon monoxide or carbon dioxide.
[0040] In Na 2+x Fe 2-x In the (SO4)3 / organic conductive polymer composite positive electrode material, the value range of x is 0≤x≤1.
[0041] Example 3 This embodiment relates to a method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material, comprising the following steps: S1. Preparation of chain products: dissolving organic conductive polymer monomers in water, adjusting the solution pH to 1, adding oxidants, inducing polymerization of organic conductive polymer monomers to form chain products. Specifically, the organic conductive polymer monomers are phenylene and diacetylene. The oxidant is sodium percarbonate, and the added molar amount of the oxidant is 3 times the molar amount of the organic conductive polymer monomer; the acid used to adjust the pH is salicylic acid and malic acid.
[0042] S2. Preparation of precursor slurry: Add sodium source, iron source and sulfur source to the solution for forming chain products, and dissolve them fully to form a uniform precursor slurry. The sodium source is sodium citrate and sodium ascorbate; the iron source is iron powder and ferrous sulfate; the sulfur source is sulfuric acid and ammonium sulfate.
[0043] S3, preparation of precursor powder: drying the above precursor slurry to achieve solid-liquid separation, and obtaining dry precursor powder. Specifically, the drying method is heating evaporation.
[0044] S4, high temperature sintering: calcine the above precursor powder in a protective atmosphere, and obtain Na after natural cooling. 2+x Fe 2-x (SO4)3 / organic conductive polymer composite positive electrode material. Specifically, the sintering temperature is 400°C, the time is 1H, and the protective atmosphere is carbon dioxide, hydrogen, or helium.
[0045] In Na 2+x Fe 2-x In the (SO4)3 / organic conductive polymer composite positive electrode material, the value range of x is 0≤x≤1.
[0046] Example 4 This embodiment relates to a method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material, comprising the following steps: S1. Preparation of chain products: dissolving organic conductive polymer monomers in water, adjusting the solution pH to 2, adding oxidants, inducing polymerization of organic conductive polymer monomers to form chain products. Specifically, the organic conductive polymer monomers are thiophene, acetylene, and diacetylene. The oxidants are hydrogen peroxide and hydrazine hydrate, and the added molar amount of the oxidants is 1.5 times the molar amount of the organic conductive polymer monomers; the acid for adjusting the pH is formic acid, salicylic acid, and malic acid.
[0047] S2. Preparation of precursor slurry: Add sodium source, iron source and sulfur source to the solution for forming chain products, and dissolve them fully to form a uniform precursor slurry. The sodium source is sodium sulfate, sodium citrate, sodium ascorbate; the iron source is ferroferric oxide, ferric oxide, ferric hydroxide; the sulfur source is sulfuric acid, ammonium sulfate, ammonium ferrous sulfate.
[0048] S3, preparation of precursor powder: drying the above precursor slurry to achieve solid-liquid separation, and obtaining dry precursor powder. Specifically, the drying method is spray drying or flash drying.
[0049] S4, high temperature sintering: calcine the above precursor powder in a protective atmosphere, and obtain Na after natural cooling. 2+x Fe 2-x (SO4)3 / organic conductive polymer composite positive electrode material. Specifically, the sintering temperature is 350°C, the time is 2H, and the protective atmosphere is nitrogen, argon, hydrogen, or helium.
[0050] In Na 2+x Fe 2-x In the (SO4)3 / organic conductive polymer composite positive electrode material, the value range of x is 0≤x≤1.
[0051] Example 5 This embodiment relates to a method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material, comprising the following steps: S1. Preparation of chain products: dissolving organic conductive polymer monomers in water, adjusting the solution pH to 3, adding oxidants, inducing polymerization of organic conductive polymer monomers to form chain products. Specifically, the organic conductive polymer monomers are aniline, pyrrole, thiophene, and acetylene. The oxidants are hydrogen peroxide and hydrazine hydrate, and the added molar amount of the oxidants is 2.5 times the molar amount of the organic conductive polymer monomers; the acid for adjusting the pH is formic acid, acetic acid, sulfuric acid, and malic acid; S2. Preparation of precursor slurry: Add sodium source, iron source and sulfur source to the solution for forming chain products, and dissolve them fully to form a uniform precursor slurry. The sodium source is sodium formate, sodium acetate, sodium sulfate, sodium citrate, sodium ascorbate; the iron source is ferrous oxide, ferric oxide, ferric oxide, ferric hydroxide; the sulfur source is sulfuric acid and ammonium sulfate.
[0052] S3, preparation of precursor powder: drying the above precursor slurry to achieve solid-liquid separation, and obtaining dry precursor powder. Specifically, the drying method is spray drying or flash drying.
[0053] S4, high temperature sintering: calcine the above precursor powder in a protective atmosphere, and obtain Na after natural cooling. 2+x Fe 2-x (SO4)3 / organic conductive polymer composite positive electrode material. Specifically, the sintering temperature is 380°C, the time is 1.5 hours, and the protective atmosphere is carbon monoxide, carbon dioxide, hydrogen, helium In Na 2+x Fe 2-x In the (SO4)3 / organic conductive polymer composite positive electrode material, the value range of x is 0≤x≤1.
[0054] Application Example 1 Na 2.4 Fe 1.8 Synthesis and electrochemical properties of (SO4)3 / polyaniline materials This embodiment relates to a high conductivity sodium ion battery positive electrode Na 2.4 Fe 1.8 (SO4)3 / polyaniline composite material. The preparation method thereof comprises the following steps: Step 1: dissolving the aniline monomer in water, adjusting the pH of the solution to 1.5 with formic acid, and slowly adding hydrazine hydrate (the added amount is 2.0 times the molar amount of the aniline monomer) to induce in-situ polymerization of the aniline monomer to form a dark brown slurry; Step 2: Add sodium acetate, ferrous sulfate and sulfuric acid into the above solution in a ratio of 2.4:1.8:1.2, and obtain a uniform precursor slurry after fully dissolving; Step 3: spray drying the above precursor solution, with an air inlet temperature of 300°C and an air outlet temperature of 90°C, to remove moisture from the slurry and obtain a dry precursor powder; Step 4: calcine the above precursor powder under nitrogen atmosphere at a sintering temperature of 400°C for 10 hours, and obtain Na 2.4 Fe 1.8 (SO4)3 / polyaniline positive electrode material.
[0055] The results in Table 1 show that Na 2.4 Fe1.8 The specific surface area of (SO4)3 / polyaniline positive electrode material is 5.6m 2 / g, compared with the materials prepared by in-situ carbon thermal reduction method and inorganic carbon physical modification method in the comparative example, the specific surface area is significantly reduced, indicating that Na 2.4 Fe 1.8 The (SO4)3 / polyaniline cathode material has a low porosity, and the particles formed during the primary particle sintering process are larger and have a higher degree of densification. 2.4 Fe 1.8 The surface of (SO4)3 or polyaniline material is smooth without too many defects, which ultimately realizes the preparation of low specific surface area materials, and has significant improvements in the back-end manufacturing of materials and the performance and maintenance of electrochemical properties.
[0056] Will Na 2.4 Fe 1.8 (SO4)3 / polyaniline positive electrode material, AB, and PVDF were mixed and slurried in a mass ratio of 9.2:0.4:0.4. The slurry viscosity was 2900Pa.S, with good fluidity. The load distribution on the current collector during the coating process was uniform, which was related to the low specific surface area of the material. The smaller the specific surface area, the weaker the adsorption capacity of the solvent and binder during the homogenization process, the lower the slurry viscosity, and the better the processing performance. After that, the black slurry was coated on aluminum foil using a 150um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100℃ for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with sodium metal as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button battery in a glove box.
[0057] The button cell was subjected to constant current charge and discharge test with a current density of 0.1C (1C=110mAh / g). The results in Table 1 show that within the voltage range of 2.0-4.5V, the reversible specific capacity of the electrode is 108.2mAh / g, and the capacity utilization is significantly higher than that of the material in the comparative example. The improvement in capacity utilization is related to the phase purity and crystallinity of the material itself. When the liquid phase method is used to prepare the material, due to the high degree of uniform ion mixing, the crystal nucleus formed by the mutual bonding between ions during the sintering process is more complete, the crystallinity is higher, the effective sodium storage sites are increased, and the capacity is improved. In addition, the results in Table 1 show that at 10C, the capacity retention rate of the material is 97.6% of 0.1C, which is better than the performance in the comparative example, showing good rate performance, indicating that the polyaniline conductive polymer has good rate performance for Na 2.4 Fe 1.8(SO4)3 material modification effectively improved the electronic conductivity of the material, increased the speed of electron transfer between particles, reduced the polarization of the material at high rates, and thus improved the utilization of its capacity at high rates. Finally, at a rate of 1C, after 500 cycles, the capacity retention rate of the electrode was as high as 97.8%, which was better than the cycle stability of the material in the comparative example. This indicates that the addition of polyaniline conductive polymer reduces the internal resistance of the material, which is beneficial to the improvement of the material's cycle stability. 2.4 Fe 1.8 The (SO4)3 / polyaniline material has a small specific surface area and high crystal density. The degree of side reaction with the electrolyte is reduced under high voltage, which effectively inhibits the dissolution of the material interface and thus improves its cycle stability.
[0058] Comparative Example 1 Liquid Phase Carbothermal Reduction Method Na 2.4 Fe 1.8 Synthesis and electrochemical properties of (SO4)3 / C materials This embodiment involves Na 2.4 Fe 1.8 (SO4)3 / C composite material. The preparation method thereof comprises the following steps: Step 1: Sodium acetate, ferrous sulfate, and sulfuric acid are added to the above solution in a ratio of 2.4:1.8:1.2, and citric acid is added as an organic carbon source in a molar amount of 0.2 times the molar amount of ferrous sulfate. After fully dissolving, a uniform precursor slurry is obtained; Step 2: spray drying the above precursor solution, with an air inlet temperature of 300°C and an air outlet temperature of 90°C, to remove moisture from the slurry and obtain a dry precursor powder; Step 3: In a nitrogen atmosphere, the precursor powder is calcined at 400°C for 10 hours. After cooling naturally, Na 2.4 Fe 1.8 (SO4)3 / C positive electrode material.
[0059] The results in Table 1 show that the specific surface area of the material is 9.7 m 2 / g, which is slightly larger than that in Application Example 1, indicating that the material has more pores, which is related to the low degree of pyrolysis of citric acid. Theoretically, citric acid can be completely and effectively cracked to form a highly conductive and densely coated carbon layer at a temperature above 500°C, while at a pyrolysis temperature of 400°C, the carboxyl, hydroxyl and other groups contained in citric acid cannot be effectively converted into gaseous compounds and volatilized, and remain in the material, resulting in a significant increase in its specific surface area.
[0060] Will Na 2.4 Fe 1.8(SO4)3 / C composite material, AB, and PVDF are mixed and slurried in a mass ratio of 9.2:0.4:0.4. The slurry viscosity is 8900Pa.S, which is higher than the material in Application Example 1. This is related to its higher specific surface area. The larger the specific surface area, the stronger the adsorption capacity for the solvent and binder in the slurry, and the easier it is to cause the viscosity of the slurry to increase, affecting the subsequent processing of the battery cell pole piece. After that, the black slurry is coated on aluminum foil using a 150um four-sided preparation device, and then the film is dried in a vacuum drying oven at 100°C for 2 hours. Use a punching machine to punch the electrode film into a disc with a radius of 0.6mm, with metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm is a PP / PE / PP three-layer diaphragm, which is assembled into a CR2016 button battery in a glove box.
[0061] The button cell was subjected to constant current charge and discharge test with a current density of 0.1C (1C=110mAh / g). The results in Table 1 show that within the voltage range of 2.0-4.5V, the reversible specific capacity of the electrode is only 64.5mAh / g, and the capacity utilization is lower than that of the material in Application Example 1. This is related to the fact that the material is prepared by carbon thermal reduction method. The organic citric acid carbon source used in this method cannot be effectively cracked at 400°C, and the formed carbon does not have high conductivity. At the same time, the incomplete pyrolysis of the carbon source will also hinder the Na 2.4 Fe 1.8 (SO4)3The melt crystallization of the material affects its crystallinity and phase purity, which ultimately leads to the obstruction of the material capacity. In addition, the rate performance test results show that at a rate of 10C, the capacity retention rate of the material synthesized by the solid-phase carbon thermal reduction method relative to 0.1C is only 56.3%, which is much lower than the performance of the material in Application Example 1. This is related to the incomplete pyrolysis of organic carbon on the surface of the material and the excessive internal resistance of the interface, which leads to the decrease in the capacity of the material at a higher rate. Finally, the results of Table 1 show that within the voltage range of 2.0-4.3V, the electrode has a capacity retention rate of only 64.2% after 500 cycles at a rate of 1C. Its lower cycle stability comes from the incomplete pyrolysis of organic carbon on the one hand, which easily leads to the aggravation of the side reaction between the electrolyte and the electrolyte at high voltage, affecting the interface stability of the material. On the other hand, the material is hindered by organic carbon during sintering, and there are problems with crystallinity and phase purity, which leads to uneven local volume expansion during sodium ion deintercalation, which easily induces lattice rupture and other problems, and ultimately leads to a decrease in the cycle stability of the material.
[0062] Comparative Example 2 Solid Phase Physical Mixing Method Na 2.4 Fe 1.8 Synthesis and electrochemical properties of (SO4)3 / high surface area carbon black materials This embodiment involves Na2.4 Fe 1.8 (SO4)3 / high specific surface carbon black composite material. The preparation method thereof comprises the following steps: Step 1: Sodium sulfate and ferrous sulfate are added to the ball mill in a ratio of 1.2:1.8, and high specific surface carbon black is added as a conductive agent, the added weight of which is 0.12 times the weight of ferrous sulfate, the ball-to-material ratio is 20:1, and the grinding time is 20 hours; Step 2: In a nitrogen atmosphere, the precursor powder is calcined at a temperature of 400°C for 10 hours. After cooling naturally, Na 2.4 Fe 1.8 (SO4)3 / high specific surface area carbon black positive electrode material.
[0063] The results in Table 1 show that the specific surface area of the material is as high as 17.8 m 2 / g, which is much higher than the material in Application Example 1. This is related to the introduction of high specific surface carbon black, which contains a large number of micropores in its structure, which easily causes the material specific surface to be too large. On the other hand, the ball milling process will grind the raw materials very finely. During the sintering process, these fine particles are hindered by the high specific surface carbon black and are difficult to melt and crystallize to form larger particles, which ultimately leads to a further increase in its specific surface.
[0064] Will Na 2.4 Fe 1.8 (SO4)3 / high specific surface carbon black material, AB, and PVDF are mixed and slurried in a mass ratio of 9.2:0.4:0.4. The viscosity of the material is as high as 34000Pa.S. The slurry has poor fluidity, is difficult to sieve, and is prone to cracks during the coating process. This is related to the large specific surface area of the material. It adsorbs the solvent and binder in the slurry to a certain extent, resulting in a significant decrease in its fluidity. After that, the black slurry is coated on aluminum foil using a 150um four-sided preparation device, and then the film is dried in a vacuum drying oven at 100℃ for 2 hours. The electrode film is punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm is a PP / PE / PP three-layer diaphragm, which is assembled into a CR2016 button battery in a glove box.
[0065] The above button cell was subjected to constant current charge and discharge test, and the current density was 0.1C (1C=110mAh / g). The results in Table 1 show that within the voltage range of 2.0-4.5V, the reversible specific capacity of the electrode is 89.3mAh / g, which is slightly worse than the material in Application Example 1, indicating that the material prepared by the solid phase method has a reduced mixing uniformity between the raw materials, resulting in a low phase purity and crystallinity of the final prepared material, as well as a reduced proportion of active substances, and a significant decrease in the actual capacity. In addition, the rate performance test results show that the capacity retention rate of the material at a rate of 10C is only 93.7% compared to 0.1C, and the rate performance is not good, which is related to the lower phase purity of the material. The presence of the impurity phase produces a large number of grain boundaries that affect the transmission between ions, causing the concentration polarization to intensify at high rates, seriously hindering the rapid migration of ions, and causing its rapid charge and discharge capability to be significantly reduced. Finally, the results in Table 1 show that within the voltage range of 2.0-4.3V, the capacity retention rate of the electrode after 500 cycles at a rate of 1C is only 87.6%. Compared with Application Example 1, the cycle stability is greatly reduced. The main reason is related to the larger specific surface area of the material. The larger the specific surface area, the higher the interface defect content. Under high voltage, it will accelerate the side reaction between the material interface and the electrolyte, resulting in continuous deterioration of the material cycle stability.
[0066] Table 1 Performance test results The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.
Claims
1. A method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material, characterized in that The following steps are involved: S1. Preparation of chain products: dissolving organic conductive polymer monomers in water, adjusting the pH of the solution to acidic, adding an oxidant, and inducing a polymerization reaction of the organic conductive polymer monomers to form chain products; S2. Preparation of precursor slurry: adding a sodium source, an iron source and a sulfur source to the solution for forming the chain product, and dissolving them fully to form a uniform precursor slurry; S3, preparation of precursor powder: drying the above-mentioned precursor slurry to achieve solid-liquid separation to obtain dry precursor powder; S4, high temperature sintering: calcine the above precursor powder in a protective atmosphere, and obtain Na after natural cooling. 2+x Fe 2-x (SO4)3 / organic conductive polymer composite positive electrode material; In Na 2+x Fe 2-x In the (SO4)3 / organic conductive polymer composite positive electrode material, the value range of x is 0≤x≤1.
2. The method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material according to claim 1, characterized in that: The organic conductive polymer is one or more of polyaniline, polypyrrole, polythiophene, polyacetylene, polyphenylene, polyphenylene acetylene and polydiacetylene; the organic conductive polymer monomer is one or more of aniline, pyrrole, thiophene, acetylene, phenylene and diacetylene.
3. The method for preparing the high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material according to claim 1, characterized in that: In step S1, the pH range is 1-4.
4. The method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material according to claim 1, characterized in that: In step S1, the oxidant is one or more of hydrogen peroxide, hydrazine hydrate, peracetic acid, and sodium percarbonate, and the added molar amount of the oxidant is 1-3 times the molar amount of the organic conductive polymer monomer.
5. The method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material according to claim 1, characterized in that: In step S4, the sintering temperature is 300-450°C, and the time is ≥0.1H.
6. The method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material according to claim 1, characterized in that: In step S3, the drying method is one of spray drying, flash drying, heating evaporation, or a combination of two or more thereof.
7. The method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material according to claim 1, characterized in that: In step S1, the acid used to adjust the pH is one or more of formic acid, acetic acid, sulfuric acid, nitric acid, citric acid, ascorbic acid, salicylic acid, and malic acid.
8. The method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material according to claim 1, characterized in that: In step S2, the sodium source is one or more of sodium formate, sodium acetate, sodium nitrate, sodium bicarbonate, sodium carbonate, sodium hydroxide, sodium sulfate, sodium citrate, and sodium ascorbate; the iron source is one or more of iron powder, ferrous sulfate, ferric hydroxide, ferrous oxide, ferroferric oxide, ferric oxide, ferric oxide, and ferric hydroxide; the sulfur source is one or more of sulfuric acid, ammonium sulfate, sodium sulfate, ferrous sulfate, and ammonium ferrous sulfate.
9. The method for preparing a high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material according to claim 1, characterized in that: In step S4, the protective atmosphere is one or more of nitrogen, argon, carbon monoxide, carbon dioxide, hydrogen, and helium.
10. A high conductivity sodium ion battery positive electrode material / organic conductive polymer composite material, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN116239154A
Sodium ferric sulfate positive electrode material as well as preparation method and application thereof
CN116613288A
Composite sodium ferric sulfate positive electrode material and preparation method thereof, positive electrode and sodium ion battery
CN116779808A
Sodium ferrous sulfate positive pole piece and preparation method thereof, sodium ion battery and electric device
CN118380548A
Pure-phase polyanionic sulfate sodium ion battery positive electrode material and preparation method therefor
WO2024212632A1
Cited By
A sulfate-based sodium-ion positive electrode material and a preparation method thereof
CN122843384A